جۆرەکانی کتێبخانە لە شارستانێتی ئیسلامیدا - رحیم, پ.ی.د. حسين محمد صالح; محمود, ئاسۆ محمد (Sulaimani Journal for Humanities, 2023)
This research studies the types of the libraries and their appearance in the Islamic civilization, because this civilization possessed many types of libraries. The Libraries in the Islamic civilization are considered one of the most important civilized and scientific institutions that played an essential role in conserving the history and cultures of other peoples and their civilizations by preserving ancient books and preventing them from damage and loss. Libraries have also played an outstanding role in the scientific and cultural life of Muslims in particular and the world in general. The purpose of the research is to display and identify the different types of libraries in the Islamic civilization; public libraries, private libraries, mosque libraries, school libraries and hospital libraries. This research also presents the most important libraries that had a significant role in the progression of science and knowledge especially in the period of the Abbasids.